REDUCING NITROGEN LOSSES AND INCREASING MAIZE PRODUCTIVITY IN ORGANIC MANURES-AMENDED SOILS BY INCREASING THE RIDGE TO FURROW PROPORTION. (16th March 2018) - IQBAL, SHAHID; ARIF, MUHAMMAD; THIERFELDER, CHRISTIAN; YASMEEN, TAHIRA; LI, TANG
SUMMARY: Nitrogen (N) losses greater than 40% in furrow-irrigated cropping systems are a common problem that substantially limits yields. Sustainable production methods are therefore required to reduce these losses and increase the yield under semi-arid conditions. A field trial was carried out to study the soil N dynamics and soil physicochemical properties in soils amended with organic manure (i.e. with poultry manure (PM), farmyard manure (FYM) and pressmud compost (PrM)). Soil N dynamics and properties were evaluated under different ridge to furrow ratios (1:1 and 2:1) as well as maize yield and profitability. When ridge to furrow ratio increased (2:1) in soils amended with PM, the inorganic and organic N status was increased and N losses were reduced. This strategy lowered soil pH, and maximized organic matter status and maize yield. The highest yield, net income and benefit–cost ratio were attained with 2:1 ridge to furrow ratio and PM amendment, being an alternative management for increasing maize productivity and profitability while improving nutrient use efficiency.